2012
DOI: 10.1128/jvi.00907-12
|View full text |Cite
|
Sign up to set email alerts
|

Paramecium bursaria Chlorella Virus 1 Proteome Reveals Novel Architectural and Regulatory Features of a Giant Virus

Abstract: The 331-kbp chlorovirusParamecium bursariachlorella virus 1 (PBCV-1) genome was resequenced and annotated to correct errors in the original 15-year-old sequence; 40 codons was considered the minimum protein size of an open reading frame. PBCV-1 has 416 predicted protein-encoding sequences and 11 tRNAs. A proteome analysis was also conducted on highly purified PBCV-1 virio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(112 citation statements)
references
References 67 publications
1
104
0
Order By: Relevance
“…The morphology and size of the six new OlVs sequenced here is typical of other characterized prasinoviruses that infect Micromonas or Ostreococcus (17,18). The particles also are morphologically similar to the much larger (165 to 190 nm) Chlorella viruses except for the spike structure at the vertex, which is not observed in prasinoviruses (45,48). Globally, they show icosahedral symmetry, like the great majority of the other dsDNA aquatic eukaryote viruses currently described (49), without any tail, in contrast to many archaeal and bacterial bacteriophages (50,51).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The morphology and size of the six new OlVs sequenced here is typical of other characterized prasinoviruses that infect Micromonas or Ostreococcus (17,18). The particles also are morphologically similar to the much larger (165 to 190 nm) Chlorella viruses except for the spike structure at the vertex, which is not observed in prasinoviruses (45,48). Globally, they show icosahedral symmetry, like the great majority of the other dsDNA aquatic eukaryote viruses currently described (49), without any tail, in contrast to many archaeal and bacterial bacteriophages (50,51).…”
Section: Discussionmentioning
confidence: 61%
“…Genomes of six viruses infecting other Mamiellophyceae (Bathycoccus, Micromonas, and Ostreococcus) have been described previously (17)(18)(19)(20). In addition, complete genomes of six viruses infecting other green algae, such as Chlorella (Trebouxiophyceae), are available (44)(45)(46). From these and the six new OlV genomes reported here, a core set of viral genes was defined at various taxonomic levels, from the seven OlVs infecting a unique host (O. lucimarinus) to a level incorporating all of the complete genome sequences of viruses that are specific to hosts of distinct green lineage classes: the Mamiellophyceae (represented by Bathycoccus, Micromonas, and Ostreococcus) and the Trebouxiophyceae (represented by Chlorella).…”
Section: Fig 1 Locations Of the Sampling Sites The Type Of Ostreococmentioning
confidence: 99%
“…(iv) The NY-2A virion protein sample lacked SOD activity, which provides indirect evidence that the PBCV-1 activity was virus encoded. (v) Finally, a PBCV-1 proteome study reported that the cvSOD protein was packaged in the virion (27). Therefore, the SOD activity detected in the PBCV-1 virion is the virus-encoded protein and not from the host.…”
Section: Resultsmentioning
confidence: 99%
“…The chloroviruses are proposed to have a common evolutionary ancestor with some other large DNA viruses, including the poxviruses, asfarviruses, iridoviruses, ascoviruses, mimiviruses, and marseilleviruses, and collectively are often referred to as nucleocytoplasmic large DNA viruses (NCLDVs) (24,25,26). The 331-kb linear genome of the chlorovirus type species, Paramecium bursaria chlorella virus 1 (PBCV-1), has 416 predicted protein coding sequences (CDSs) (27). About 40% of the predicted CDSs resemble those for known proteins (23), including a gene, a245r, which encodes a putative Cu-Zn SOD.…”
mentioning
confidence: 99%
“…The large number of proteins in PBCV-1 raised the issue of why giant viruses contain so many genes (45). We propose that a partial answer is provided by the current report, which highlights the elaborate and highly dynamic protein composition of VFs.…”
Section: Figmentioning
confidence: 80%